2011
DOI: 10.1017/s1047951111001272
|View full text |Cite
|
Sign up to set email alerts
|

Rapid control of foetal supraventricular tachycardia with digoxin and flecainide combination treatment

Abstract: Flecainide and digoxin combination treatment offers a safe and effective treatment for foetal supraventricular tachycardia with fast restoration of sinus rhythm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 21 publications
5
34
1
1
Order By: Relevance
“…In our study population, 64% had SVT and 36% had AF, which is a common distribution. Previous studies using several therapeutic strategies showed success rates between 60% and 95% in patients with SVT and data from 2000 onwards are summarized in Table . In our SVT group, the overall efficacy of sotalol as a single‐drug therapy was 78%, which is comparable to the conversion rate recently reported by Jaeggi et al in 35 fetuses receiving sotalol.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In our study population, 64% had SVT and 36% had AF, which is a common distribution. Previous studies using several therapeutic strategies showed success rates between 60% and 95% in patients with SVT and data from 2000 onwards are summarized in Table . In our SVT group, the overall efficacy of sotalol as a single‐drug therapy was 78%, which is comparable to the conversion rate recently reported by Jaeggi et al in 35 fetuses receiving sotalol.…”
Section: Discussionsupporting
confidence: 73%
“…Sustained tachycardias, in particular, are associated with fetal hydrops, neurological morbidity and intrauterine death. Several retrospective studies on prenatal diagnosis and management have been published, which describe the use of sotalol, digoxin and/or flecainide as single‐drug or combination therapy. In a recently published retrospective multicenter study, Jaeggi et al reported sotalol to be less effective in treatment of SVT than either digoxin or flecainide.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-six fetuses (96%) responded to flecainide and digoxin combination, with complete resolution of tachycardia in 22 (81.4%) and rate control in the other 4. 2 The authors observed slower cardioversion rates in AF, fetal hydrops, and incessant arrhythmia, and the arrhythmia-related mortality was 17% in fetal hydrops. 1 Fetal SVT and AF are most commonly accessory pathway-mediated arrhythmias.…”
Section: To the Editormentioning
confidence: 95%
“…1 Fetal SVT and AF are most commonly accessory pathway-mediated arrhythmias. 2,3 Digoxin as a single agent is not recommended to be used in SVT with accessory pathway because it blocks atrioventricular nodal conduction, and in the presence of an accessory pathway with AF or fibrillation, this might facilitate rapid antegrade conduction over the accessory pathway. 4 Electrophysiologically it would be more desirable to block not only atrioventricular nodal, but also the accessory pathway conduction to achieve clinical response in fetal AF.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation